2015
DOI: 10.1007/s10856-014-5331-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bone marrow concentrate and hyperbaric oxygen therapy on bone repair

Abstract: Neoangiogenesis represents an essential part of bone regeneration. Therefore the improvement of neovascularization is the subject of various research approaches. In addition autologous mesenchymal stem cells concentrate in combination with bone substitute materials have been shown to support bone regeneration. In a rabbit model we examined the proposed synergistic effect of hyperbaric oxygen therapy (HBOT) and bone marrow concentrate (BMC) with porous calcium phosphate granules (CPG) on neoangiogenesis and oss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Compared to other systems such the reamer-irrigator-aspirator [27] or bone aspiration techniques with or without density gradient cell centrifugation (e.g., the Harvest ® system [28], ASPIRE™ Bone Marrow Harvesting System [29]), no additional surgical approach or device material is required. Other groups prefer platelet-rich plasma (PRP) or other products from the peripheral blood to treat bone defects [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other systems such the reamer-irrigator-aspirator [27] or bone aspiration techniques with or without density gradient cell centrifugation (e.g., the Harvest ® system [28], ASPIRE™ Bone Marrow Harvesting System [29]), no additional surgical approach or device material is required. Other groups prefer platelet-rich plasma (PRP) or other products from the peripheral blood to treat bone defects [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbaric chamberRev Osteoporos Metab Miner. 2020;12(1):28-31 ORIGINALS ment in angiogenesis, increased vascularization of the aspirated iliac crest of mice19 , greater cell proliferation20 or acceleration in the healing of open femoral fractures in experimental animals…”
mentioning
confidence: 99%
“…Thom et al found that HBO treatment mobilizes stem/progenitor cells (SPCs) in healthy people and patients after radiotherapy for head and neck tumors [80]. Animal studies show promising results of HBO combination with MSCs cell therapy in repair of traumatic brain injury, bone repair and spinal cord rehabilitation, which suggests that it may also be useful in wound healing promotion [81][82][83]. However, there are no well-controlled human studies indicating the efficiency of such therapy and, taking into consideration the sensitivity of transplanted cells, it would have to be used with caution.…”
Section: Cell Therapies For Chronic Wound Treatmentmentioning
confidence: 99%